Implementation of the Entrepreneurship Capability Improvement Program in the Tourism Sector in Manado City - Florence D. J. Lengkong; Joorie M. Ruru; Very Y. Londa (Journal La Bisecoman, 2022)
Tourism and entrepreneurship are related to strengthening the country's economy, income and community welfare. The growth of business actors in the tourism sector needs to continue to be improved in terms of quality and quantity. So various programs have been carried out by the government related to the implementation of programs to increase entrepreneurial abilities. Using a qualitative design, this research was conducted to examine the implementation of an entrepreneurial capacity building program in Manado City. Research findings show that the "human error" factor in business management and less innovative product quality are problems currently being faced. The Manado City Government, through Regional Work Units and in collaboration with the Central Government and the Private Sector, has implemented a program to increase entrepreneurial capacity in the form of socialization, training, mentoring, protection and provision of facilities. There has been an increase in the quantity of business actors but not yet in the quality of business management. Therefore, there needs to be good synergy between the government and business actors in supporting the tourism sector through entrepreneurial activities.